(Bio)Sensing Strategies Based on Ionic Liquid-Functionalized Carbon Nanocomposites for Pharmaceuticals: Towards Greener Electrochemical Tools - Torrinha, Álvaro (2022)
The interaction of carbon-based nanomaterials and ionic liquids (ILs) has been thoroughly exploited for diverse electroanalytical solutions since the first report in 2003. This combination, either through covalent or non-covalent functionalization, takes advantage of the unique characteristics inherent to each material, resulting in synergistic effects that are conferred to the electrochemical (bio)sensing system. From one side, carbon nanomaterials offer miniaturization capacity with enhanced electron transfer rates at a reduced cost, whereas from the other side, ILs contribute as ecological dispersing media for the nanostructures, improving conductivity and biocompatibility. The present review focuses on the use of this interesting type of nanocomposites for the development of (bio)sensors specifically for pharmaceutical detection, with emphasis on the analytical (bio)sensing features. The literature search displayed the conjugation of more than 20 different ILs and several carbon nanomaterials (MWCNT, SWCNT, graphene, carbon nanofibers, fullerene, and carbon quantum dots, among others) that were applied for a large set (about 60) of pharmaceutical compounds. This great variability causes a straightforward comparison between sensors to be a challenging task. Undoubtedly, electrochemical sensors based on the conjugation of carbon nanomaterials with ILs can potentially be established as sustainable analytical tools and viable alternatives to more traditional methods, especially concerning in situ environmental analysis